Arah Baru Pendidikan Islam: Membangun Epistemologi Pendidikan Islam Monokhotomik - Zamroni Zamroni (UIN Sultan Aji Muhammad Idris Samarinda, 2010)
As an agent of civilization and social change, Islamic education in an atmosphere of modernization and globalization demanded to play a role in a dynamic and proactive. Its presence is expected to contribute meaningful and positive change for the improvement and advancement of the Muslim civilization, both on theoretical and practical intellectual terrain. Islamic education is not merely a process of transformation of moral values to shield themselves from negative access globalization and modernization. But the most urgent is how the moral values that have been inculcated through Islamic education is able to take an active role as a generator that has a liberatory power of social pressure and the crush of cultural backwardness, ignorance, economic and poverty in the midst of rapid social mobility. Therefore we need a constructive effort by building monokhotomik Islamic education. This epistemological approach provides an understanding and an integral and comprehensive skills. Someone who knows something of the process must know the outcome. Conversely, many who know the results but do not know the process. Unlike students who are given only bread and then she enjoyed it, with students who are invited to make bread, then enjoy it. Of course, knowledge of learners who know the process of making bread to enjoy it more complete, robust, and memorable.